Processing : a programming handbook for visual designers and artists. - Reas, Casey, ....-; Fry, Ben, ....- (London : MIT, 2007)
It has been more than twenty years since desktop publishing reinvented design, and it's clear that there is a growing need for designers and artists to learn programming skills to fill the widening gap between their ideas and the capability of their purchased software. This book is an introduction to the concepts of computer programming within the context of the visual arts. It offers a comprehensive reference and text for Processing (www.processing.org), an open-source programming language that can be used by students, artists, designers, architects, researchers, and anyone who wants to program images, animation, and interactivity.